2017
DOI: 10.1186/s12913-017-2393-y
|View full text |Cite
|
Sign up to set email alerts
|

Building COPD care on shaky ground: a mixed methods study from Swedish primary care professional perspective

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a public health problem. Interprofessional collaboration and health promotion interventions such as exercise training, education, and behaviour change are cost effective, have a good effect on health status, and are recommended in COPD treatment guidelines. There is a gap between the guidelines and the healthcare available to people with COPD.The aim of this study was to increase the understanding of what shapes the provision of primary care services to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(76 citation statements)
references
References 46 publications
3
73
0
Order By: Relevance
“… 63 To facilitate implementation of the guidelines, several actions are needed, such as additional resources, further training for professionals, and improved organizational structure for interprofessional collaboration and patient education. 64 …”
Section: Discussionmentioning
confidence: 99%
“… 63 To facilitate implementation of the guidelines, several actions are needed, such as additional resources, further training for professionals, and improved organizational structure for interprofessional collaboration and patient education. 64 …”
Section: Discussionmentioning
confidence: 99%
“…Physicians use it, albeit rarely, in combination with telemetric information for clinical decision making. The decision making process is not based on any single value, such as may be the case in diabetes [60] as COPD patients are multi-morbid, elderly, with a particular social profile [57,61]. Comparing the three CLDs, some variables are present in all of them, while some are unique for a particular HCP.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nurses observed that they need to better understand the patient's character, which in most cases in COPD care is self-inhibiting. This means that patients with COPD do not like to bother anyone, even if they experience a disease crisis [57]. "Adoption" increased "Adoption (Patient)", which created an indirect reinforcing loop for "Adoption".…”
Section: Plos Onementioning
confidence: 99%
“…Wagner’s chronic care model36 37 underpins many current models of COPD care38 39 with its emphasis on the need for proactive, planned and integrated care across the health system. While there is international13 and NZ40 evidence from randomised clinical trials that integrated disease management for COPD improves patients’ quality of life and reduces hospital admissions, the integration of these models into routine clinical practice remains problematic 41 42. One key problem is fragmentation of care41 and the NZ health system, including the Southern health region,43 44 compares unfavourably with other health systems in terms of the degree of care fragmentation,45 a problem exacerbated by the primary care copayment funding model 43 46.…”
Section: Discussionmentioning
confidence: 99%
“…While there is international13 and NZ40 evidence from randomised clinical trials that integrated disease management for COPD improves patients’ quality of life and reduces hospital admissions, the integration of these models into routine clinical practice remains problematic 41 42. One key problem is fragmentation of care41 and the NZ health system, including the Southern health region,43 44 compares unfavourably with other health systems in terms of the degree of care fragmentation,45 a problem exacerbated by the primary care copayment funding model 43 46. Our findings of barriers to accessing integrated care (availability, affordability, appropriateness and ability to pay) are consistent with this literature.…”
Section: Discussionmentioning
confidence: 99%